Learners’ preparedness for higher education in South Africa: developing a sense of academic belonging through the selective learning approach - Mabulana, Katlego (Frontiers in Education, 2025)
IntroductionThe high drop-out rates at South African universities have raised concerns regarding the Curriculum Assessment Policy Statements’ (CAPS) ability to prepare learners for the world beyond secondary education. This study sought to investigate teachers’ perceptions of how the Selective Learning Approach (SLA), based on Multiple Intelligences Theory, can enable learners to transition to higher education and find academic belonging seamlessly. Specifically, the focus was on the suitability of transitional processes, including the curriculum programmes in secondary education to prepare learners for higher education.MethodsTo conduct this investigation, a qualitative methodological approach was adopted which employed semi-structured interviews as a means of data collection. The study’s purposively selected sample consisted of eight teachers in the Motheo Education District, Mangaung. A thematic analysis method was utilized to analyze the data.ResultsThe findings indicated that the Selective Learning Approach can foster a sense of belonging among learners transitioning from secondary to higher education in South Africa which is crucial for their academic success in higher education. This includes a deliberate focus on vertical articulation (continuous learning) in basic education, higher education programme choices, and workload management.DiscussionFurthermore, the study provided recommendations on mitigating measures for factors that affect effective academic belonging in South African schools. The emphasis on vertical articulation in the findings supports the conceptual framework’s proposition that curriculum continuity is essential for successful higher education transitions.